2011
DOI: 10.1007/s00774-011-0286-4
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis onset differences between rural and metropolitan populations: correlation to fracture type, severity, and treatment efficacy

Abstract: Osteoporosis is the prevalent cause of fractures in an ever-aging population, with an established correlation between daily activities and way of life. We aimed to delineate differences in onset of osteoporosis, T-score progression, quality of life, and correlation to prevalence, types, and severity of fractures in age-comparable populations of rural and metropolitan habitats in this multicenter, retrospective double-blind study. We evaluated data derived from the medical files of two comparable groups of oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Pagonis et al reported that osteoporotic fracture patterns in urban patients are more severe, which is explained by decreased activity level and poor quality of life (23). In the same study, the authors stated that people living in rural areas had a later diagnosis of osteoporosis, and had better treatment outcomes (23).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Pagonis et al reported that osteoporotic fracture patterns in urban patients are more severe, which is explained by decreased activity level and poor quality of life (23). In the same study, the authors stated that people living in rural areas had a later diagnosis of osteoporosis, and had better treatment outcomes (23).…”
Section: Resultsmentioning
confidence: 74%
“…In the same study, the authors stated that people living in rural areas had a later diagnosis of osteoporosis, and had better treatment outcomes (23). Men aged >60 years living in rural areas are more active than their urban counterparts, because of work and environmental conditions (24).…”
Section: Resultsmentioning
confidence: 94%
“…However, lifestyle might not influence BMD directly or relatively influence bone size [ 27 ]. Additionally, osteoporosis diagnoses have been confirmed earlier in rural areas than in urban areas [ 28 ]. We found a more hazardous effect of PM 10 on osteoporosis incidence in less urbanized areas.…”
Section: Discussionmentioning
confidence: 99%
“…In older adults, loss of bone mass will occur, but maintaining physical activity levels (including weight-bearing and strength training components) can help to minimize the decrease in bone mineral density [29,51,53e56]. Older adults who live in rural areas and may therefore have more active lifestyles have a later onset of osteoporosis and less severe osteoporotic fractures than those who live in metropolitan areas [57].…”
Section: Maximizing Bone Health and Growth Through Physical Activitymentioning
confidence: 99%